1999
DOI: 10.1016/s1074-7613(00)80123-5
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Blockade Reverses CD8+ T Cell Tolerance to Tumor by a CD4+ T Cell– and IL-2-Dependent Mechanism

Abstract: A tumor-specific CD8+ T cell response was studied using adoptive transfer of OT-I TCR transgenic cells. Upon i.p. challenge with E.G7 tumor, OT-I cells undergo CD4+ T cell-independent expansion at the tumor site and develop lytic function. Before tumor elimination, however, they leave the peritoneal cavity (PC) and appear in the LN and spleen where they exhibit "split anergy" and cannot further proliferate to antigen. Administering anti-CTLA-4 mAb early caused sustained OT-1 expansion in the PC, and late admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
209
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(226 citation statements)
references
References 40 publications
16
209
1
Order By: Relevance
“…The potential contribution of T cell immunity in the therapeutic effectiveness of the combination regimen investigated in this study is further supported by the highest degree of CD3 C infiltrating cells identified in TS/A tumors from mice treated with 5-AZA-CdR and mAb 9H10. Consistent with previous observations demonstrating that tumor-specific immune responses induced by immune checkpoint blockade depend on both CD4 C and CD8 C T cells, 22,23 the lymphocyte tumor infiltration comprised both CD4 C and CD8 C T cells.…”
Section: Discussionsupporting
confidence: 92%
“…The potential contribution of T cell immunity in the therapeutic effectiveness of the combination regimen investigated in this study is further supported by the highest degree of CD3 C infiltrating cells identified in TS/A tumors from mice treated with 5-AZA-CdR and mAb 9H10. Consistent with previous observations demonstrating that tumor-specific immune responses induced by immune checkpoint blockade depend on both CD4 C and CD8 C T cells, 22,23 the lymphocyte tumor infiltration comprised both CD4 C and CD8 C T cells.…”
Section: Discussionsupporting
confidence: 92%
“…First, CTLA-4 blockade may augment responsiveness by facilitating the participation in the response of T cells with TCRs that have high affinity for the p53 261-269 epitope. Consistent with this possibility, it has been described that anti-CTLA-4 treatment may reverse CD8 ϩ T cell tolerance to a tumor-expressed Ag by reversing anergy (21). Alternatively, the presence of anti-CTLA-4 may result in the enhanced expansion of the low-avidity p53-specific CTL that are usually found to respond in these mice.…”
Section: Anti-ctla-4 Treatment Augments the Frequency Of The Lowaffinmentioning
confidence: 68%
“…However, the precise mechanism by which CTLA-4 blockade augments antitumor responses in vivo remains unclear. Whereas some studies have shown a direct effect by anti-CTLA-4 on enhancement of CD8 ϩ T cell responses in vivo (19,20), other studies suggest that this may be indirect and mediated through the influence of anti-CTLA-4 on CD4 ϩ T cell help (21). There is also controversy regarding the ability of anti-CTLA-4 to prevent and/or reverse T cell tolerance in vivo (21)(22)(23).…”
mentioning
confidence: 99%
“…In spite of the recognized importance of Ag-specific CD4 1 T cells in both adaptive and innate immune responses, their identification remains elusive, and their in vitro amplification is hindered by the absence of reliable protocols able to support cell proliferation in the absence of terminal differentiation. While, Ag tumours elicit natural tumour-specific CD4 1 T-cell responses [4][5][6][7][8][9][10], functional tolerance is eventually observed through the induction of T-cell anergy [11,12], T-cell depletion [13] or the limitation of the memory repertoire [10,14,15]. This is possibly due to Ag persistence, and continual TCR signaling, as in the case of chronic viral infections [16][17][18].…”
Section: Introductionmentioning
confidence: 99%